1994
DOI: 10.1227/00006123-199412000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Chronic Hypertrophic Craniocervical Pachymeningitis

Abstract: A 55-year-old woman with a unique form of chronic hypertrophic pachymeningitis involving the posterior fossa and upper cervical spine is reported. Unlike other cases previously described, the clinical picture was dominated by signs of increased intracranial pressure, lower cranial nerve disorders, and a progressive cervical radiculomyelopathy. The diagnosis was made by means of a contrast-enhanced magnetic resonance imaging scan and confirmed by histological examination of the excised dura. Surgical treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…Locations of the thickened dura matter differ among different causes. The posterior fossa was the most affected area in idiopathic HP and tuberculous meningitis HP according to our study, which was also reported in other studies [6,8,9]. It is notable that posterior fossa HP can cause acute noncommunicating hydrocephalus [9].…”
Section: Imaging Featuressupporting
confidence: 89%
See 2 more Smart Citations
“…Locations of the thickened dura matter differ among different causes. The posterior fossa was the most affected area in idiopathic HP and tuberculous meningitis HP according to our study, which was also reported in other studies [6,8,9]. It is notable that posterior fossa HP can cause acute noncommunicating hydrocephalus [9].…”
Section: Imaging Featuressupporting
confidence: 89%
“…Therefore, patients with otitis media or concurrent multiple cranial nerve deficits should receive contrast-enhanced MRI to rule out HP. In addition, the involvement of the junction of the craniocervical area has been reported in several cases [8,24] and causes obstructive hydrocephalus along with cerebellar tonsillar herniation.…”
Section: Imaging Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Corticosteroid therapy has been effective in alleviating the symptoms and arresting the progression of HCP, but a relapse frequently occurs when the dosage is tapered (2,3,10). The immunosuppressive drugs, such as azathioprine (3,26) and cyclophophamide (3,13), have shown variable efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…It often causes headache and multiple cranial nerve palsies due to fibrous entrapment or ischemic damage. 1,2 Although several causes, either infectious or autoimmune, have been suggested, most aspects of this rare disease remain to be elucidated. It is usually diagnosed by contrast-enhanced magnetic resonance imaging (MRI) or histologic examination of the excised dura.…”
Section: Introductionmentioning
confidence: 99%